Empowering and sustaining government tax revenue through tax information on social media in Malaysia - Mohd Allif Anwar Abu Bakar; Nelson Lajuni; Sharifah Milda Amirul; Saizal Pinjaman (Universiti Malaysia Sabah, 2024)
Sustainable government tax revenue plays a significant role in many developing countries, especially in the current economic situation. In today’s digital age, people increasingly turn to social networks for information and assistance, leading to essential considerations about how these platforms may influence behaviour. This study aims to create a conceptual framework for the effect of tax information on social media towards tax revenue in Malaysia. Three constructs of tax information via social media were considered: Tax Information Availability (TIA), Tax Informational Quality (TIQ) and Tax Informational Influence (TII). The proposed framework may aid future research by offering a systematic means of evaluating taxin formation on social media as a determinant of influencing tax revenue. The framework may also provide measures to sustain government revenue and determine how tax authorities can design targeted social media outreach programs to better comprehend taxpayer compliance behaviour. This study offers an appropriate mechanism of social media variables as a factor of tax revenue for further analysis and discussion.